2019
DOI: 10.1039/c9ra09351f
|View full text |Cite
|
Sign up to set email alerts
|

Efficient tri-metallic oxides NiCo2O4/CuO for the oxygen evolution reaction

Abstract: In this study, a simple approach was used to produce nonprecious, earth abundant, stable and environmentally friendly NiCo2O4/CuO composites for the oxygen evolution reaction (OER) in alkaline media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 74 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…This assumption supports the volcano trend in the overpotential (Figure S14) as a function of the Cu amount observed in present work. However, such trend might also be attributed to the change of the resistance and formation of more active intermediate species on the surface of the metal oxides, which is caused by Fe−Cu/Ni interactions [12,58] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This assumption supports the volcano trend in the overpotential (Figure S14) as a function of the Cu amount observed in present work. However, such trend might also be attributed to the change of the resistance and formation of more active intermediate species on the surface of the metal oxides, which is caused by Fe−Cu/Ni interactions [12,58] …”
Section: Resultsmentioning
confidence: 99%
“…However, such trend might also be attributed to the change of the resistance and formation of more active intermediate species on the surface of the metal oxides, which is caused by FeÀ Cu/Ni interactions. [12,58] The Tafel plots extracted from the LSV curves before and after 200 CVs are shown in Figure 3c,d and the values are stated in Table S3. The initial Tafel slope values are within the range of 50-56 mV dec À 1 for all the catalysts, except CuCo (71 mV dec À 1 ) implying slower kinetics of the reaction catalyzed by this oxide.…”
Section: Chemsuschemmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1999, Tavares and his colleagues concluded that the substitution of Cu(II) in the NiCo 2 O 4 spinel lattice leads to significant changes in surface composition and oxygen evolution [ 18 ]. Meanwhile, Mugheri et al also reported OER performance on NiCo 2 O 4 /CuO electrode active material: 0.5 g of CuO on NiCo 2 O 4 showed a low starting potential of 1.46 V, and a current density of 10 mA cm −2 was achieved at an electrode potential of 230 mV, and the durability was maintained for 35 h [ 19 ]. On the other hand, due to the similar physical properties of Ni and Co, the preparation of nickel-cobalt bimetal oxide of NiCo 2 O 4 is relatively simple and a pure phase structure is easily formed.…”
Section: Introductionmentioning
confidence: 99%